Neuroform EZ Stent for Late Thrombosis after Carotid Intracranial Stenosis: A Case Report and Literature Review (Global Journal of Medical Research, 2020)
The patient was a 44-year-old male. He came to Fenggang People's Hospital in Dongguan City, Guangdong Province for left limb weakness in November 2019. His NIHSS score on admission was 1 point. The diagnosis was as follows: 1. acute watershed infarctions in the bilateral cerebral hemispheres; 2. occlusion of the right internal carotid artery (segment C6) and left internal carotid artery; 3. hyperlipidaemia; 4. prior bilateral occipital lobe old cerebral infarction, treated with aspirin 100 mg qd and atorvastatin 40 mg qn. Following the treatment of the previous infarction, the patient's symptoms had improved, and he had been discharged with an NIHSS score of 0 points.
Keywords: stent; thrombosis; intracranial artery stenosis